Edukasi Pemanfaatan Limbah Padat Tahu menjadi Karbon Aktif di Desa Mangunjaya Kabupaten Bekasi - Saing, Bungaran; Kusumawati, Amora; Fais, Muhammad Hanif Ilham; Agustian, Dinda Yesika; Amalia, Rizky Yusrina; Sukreni, Tulus (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Tofu, non-fermented soybean curd is a nutritious and easily digestible product with high quality protein. The procedure for making tofu includes soaking the beans, grinding, filtering, boiling, coagulating, and molding. Mangunjaya Village is one of the tofu-producing areas in Bekasi. Tofu processing produces liquid and solid waste. So far, the solid waste known as tofu dregs from tofu production in Mangunjaya Village is only production waste that has no value. So that in this educational activity, the community around the tofu factory in Mangunjaya Village was trained to utilize tofu dregs in activated carbon. Activated carbon from tofu dregs can be used in clarification of used cooking oil. The purpose of this educational activity is to increase public awareness to process tofu solid waste so as not to damage the ecosystem and help improve the community's economy.